Control Al/Mg intermetallic compound formation during ultrasonic-assisted soldering Mg to Al - Xu, Zhiwu; Li, Zhengwei; Li, Jiaqi; Ma, Zhipeng; Yan, Jiuchun (Ultrasonics sonochemistry, 2018)
•The formation of the intermetallic compounds of Al3Mg2 and Al12Mg17 was avoided by using Sn-based filler metals.•A new intermetallic compound of Mg2Sn formed and it was prone to cracks at large thickness.•The formation of Mg2Sn was significantly depressed by using Sn-9Zn and decreasing soldering temperature.•The addition of Zn in Sn-based filler metal prevented Sn whiskers.•A cavitation model during ultrasonic assisted soldering was proposed. To prevent the formation of Al/Mg intermetallic compounds (IMCs) of Al3Mg2 and Al12Mg17, dissimilar Al/Mg were ultrasonic-assisted soldered using Sn-based filler metals. A new IMC of Mg2Sn formed in the soldered joints during this process and it was prone to crack at large thickness. The thickness of Mg2Sn was reduced to 22 μm at 285 °C when using Sn-3Cu as the filler metal. Cracks were still observed inside the blocky Mg2Sn. The thickness of Mg2Sn was significantly reduced when using Sn-9Zn as the filler metal. A 17 μm Mg2Sn layer without crack was obtained at a temperature of 200 °C, ultrasonic power of Mode I, and ultrasonic time of 2 s. The shear strengths of the joints using Sn-9Zn was much higher than those using Sn-3Cu because of the thinner Mg2Sn layer in the former joints. Sn whiskers were prevented by using Sn-9Zn. A cavitation model during ultrasonic assisted soldering was proposed.